Implementasi Lembar Aktivitas Berbasis Pendekatan Saintifik untuk Meningkatkan Penalaran Spasial dan Self Esteem pada Mahasiswa Matematika - Westi Bilda; Dian Nopitasari; Desty Haswati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
Activity sheet is one of the tools that can be used in the learning activities by applying the desired learning steps. The aim of this study is to find out there is an increase in spatial reasoning and self esteem of students after using a scientific-based activity sheet on Geometri Analitik Datar subject. This type of research is one-group pretest-posttets design conducted by researchers before and after scientific-based activity sheets as treatment of this research. The subjects of this study were the second semester students who are learning Geometri Analitik Datar course consisted of 30 students. The research instruments used ware spatial reasoning test in the form of multiple choice tests and a self esteem questionnaire. The technical analysis used were a descriptive analysis and N-Gain analysis. The result of the research on spatial reasoning shows the pretest average score is 58.83 and the posttest average score is 76.17. It means that there is a significant increasing result between pretest and posttest that is 17.34. While the result of self esteem shows the pretest average score is 52.07 and the posttest average score is 73.60. It means that there is a significant increasing result in self esteem result that is 21.53. The results of the spatial reasoning and self esteem gain distribution range, both of them included medium criteria, that is 80%. Thus it can be concluded that the spatial reasoning and self esteem of students increases after applying learning using a scientific approach based activity sheet.